ANALISIS PENGENDALIAN KUALITAS TERHADAP PRODUKSI PALM KERNEL DENGAN MENGGUNAKAN METODE LEAN SIX SIGMA - Suseno Suseno; Muhammad Amin Adam (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2022)
Abstrak: Based on the data analysis on the quality improvement program using lean six sigma that has been carried out, the following conclusions can be drawn: From 1 month of observation of defects in PT Sultra Prima Lestari's cloth masks, it is known that the DPMO value and the sigma value still do not meet the ideal number, which is 3.4 failures per million opportunities. With an average DPMO value of 141,614 and a sigma value of 5.1, it shows that the palm kernel oil production process has not yet reached the target of improving the quality of Six Sigma, namely reaching a sigma level of 6 Sigma (6σ), so it is necessary to make continuous improvements to palm kernel oil production process at PT Sultra Prima Lestari.After analyzing using this method, there are 4 types of product defects at PT Sultra Prima Lestari. Factors that cause product defects, namely labor (human), materials, equipment, and methods. Efforts that can be made to overcome product defects of PT Sultra Prima Lestari based on the DMAIC concept, include: Humans: Workers can improve the quality of masks by carrying out SOPs on materials and tools, then double checking the whole process.Material: Materials or materials can be improved in quality by choosing fresh fruit that is not easy to mold, of high quality, and according to SOPs. Equipment: The durability of the equipment used can be increased by carrying out routine maintenance on a monthly schedule and equipment components that have been damaged can be replaced by purchasing new and high-quality equipment components. Methods: Palm kernel oil production methods can be improved by implementing SOPs and double checking Keywords : Define, Measure, Analyze, Inprove, Control